SAT0252 Cartilage Glycoprotein 39 (YKL-40) Correlates with Functional Disability and Basri in Ankylosing Spondylitis Patients. (9th June 2015) - Pinto-Tasende, J.; Alonso Blanco, E.; Bejerano, C.; Gromaz, J.; Silva, M.T.; Fernandez-Lopez, C.; Oreiro, N.; Freire, M.; De Toro, F.; Blanco García, F.
Abstract : Background: Diseases with inflammation and damage of joints lead to tissue degradation and YKL-40 may be as a marker of this fact. Ankylosing spondylitis (AS) exhibit higher levels of plasma YKL-40 compared with healthy controls. Spine and sacroiliacs joints are the main target of inflammation in AS and structural damage led to limitation of mobility and disability of patients. Objectives: To evaluate YKL-40 serum levels in relation with structural damage and metrology in a longitudinal observational cohort of anti-TNF naïve AS patients. Methods: Data from patients with diagnoses of AS (modified NY criteria) included demographic characteristics (age, gender, disease duration, body mass index-BMI), Metrology (cervical rotation, occiput to wall distance, chest expansion, lumbar lateral flexion, modified Schober's, finger to floor distance and intermalleolar distance), BASDAI and BASFI scores, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP). Radiographs of these patients were obtained and scored according to the Bath AS Radiology Index-spine (BASRI-s) at baseline (BASRI-spine, range 2-12; sacroiliac joints, AP and lateral views of lumbar spine, lateral view of cervical spine). Serum levels of YKL-40 were determined by ELISA (ng/ml) in blood samples at the entry in the cohort. Data are presented as mean (standard deviation). Correlations were assessed using the Spearman's rho correlation coefficient. P-values <0.05 were considered statistically significant. Results: Data were available on 100 patients, 82 male (82.0%), mean of age 48.7 (12.9) years, disease duration 12.5 (8.9) years and BASRI-s score 7.4 (3.5). Serum level mean (SD) of YKL-40 obtained from 86 patients was 125.9 (89.9) and had correlation with age (r 0.54; p<0.0001), disease duration (r 0.27; p 0.011), BMI (r 0.26; p 0.017), BASFI (r 0.41; p<0.0001), cervical rotation (p 0.002), occiput-to-wall distance (r 0.28; p 0.007), chest expansion (r -0.33; p 0.005), modified Schober test (r -0.30; p 0.017), finger-to-floor distance (r 0.28; p 0.008), intermalleolar distance (r -0.40; p<0.0001) and BASRI-s (r 0.38; p<0.0001). Differences had not statistical significance with regard to lumbar lateral flexion (r -0.24; p 0.059) and not correlation was seen with gender (p 0.387), ESR (r 0.13; p 0.223), CRP (r -0.13; p 0.235) and BASDAI (r 0.08; p 0.425). Moreover, BASRI-s correlated with disease duration (r 0.51; p<0.0001) and with age (r 0.52; p<0.0001). Conclusions: In our study serum levels of YKL-40 correlated with worsening of functional ability (metrology and BASFI) and axial structural damage (BASRI-spine) like disease progression in ankylosing spondylitis. References: Pedersen SJ et al. Radiographic progression is associated with resolution of systemic inflammation in patients with axial spondylarthritis treated with tumor necrosis factor α inhibitors: a study of radiographic progression, inflammation on magnetic resonance imaging, and circulating biomarkers of inflammation, angiogenesis, and cartilage and bone turnover. Arthritis Rheum. 2011 Dec;63(12):3789-800. doi: 10.1002/art.30627. Disclosure of Interest: None declared